Financing Low-Carbon Urban Transport through Subnational Green Bonds: A Review in Emerging Economies - Liongson, Edward; Nainggolan, Yunieta Anny (Integrasi Sains Media, 2025)
Subnational green bonds offer promising potential to finance low-carbon urban transport in emerging economies but remain underutilized due to a range of systemic barriers. This study uses a narrative literature review to examine how green bonds have evolved globally and how they are applied at the municipal level in the transport sector. Drawing from academic literature, multilateral reports, and real-world case studies, it identifies six persistent challenges: fragmented project pipelines, weak MRV systems, difficulties with ESG integration, legal and regulatory hurdles, low municipal credit ratings, and limited investor appetite. Despite the growth of the global green bond market, only a small share supports subnational urban transport projects. Cases such as Mexico City and Johannesburg demonstrate that the absence of enabling frameworks hinders feasibility but broader replication. This review contributes to the climate finance literature by advancing its scholarship by shifting attention from national-level instruments to local institutional realities and proposing five future research directions to support more inclusive and viable green bond mechanisms for sustainable transport in emerging markets.